Modulation of gene expression in rat muscle cells following treatment with nanoceria in different gravity regimes. (18th October 2018) - Genchi, Giada Graziana; Degl'Innocenti, Andrea; Salgarella, Alice Rita; Pezzini, Ilaria; Marino, Attilio; Menciassi, Arianna; Piccirillo, Sara; Balsamo, Michele; Ciofani, Gianni
Aim: Oxidative stress (OS) is strictly associated with senescence/pathogenesis of biological systems. As putative countermeasure to environmental OS, cerium oxide nanoparticles (nanoceria [NC]) were administered to muscle cells on ground and aboard the International Space Station.Materials & methods: Transcriptional analyses were conducted through microarray technology and hierarchical clustering. Venn diagram and gene ontology analyses were also performed on selected gene lists.Results: Adaptive responses to both NC administration and to permanence in real microgravity conditions occurred. Enrichment in the biological processes related to aging, body fat development and mesodermal tissue proliferation for NC-treated samples were found.Conclusion: Nanotechnology antioxidants promise applications to pathological conditions governed by OS on Earth and in life-hostile environments (low Earth orbit and deep space).